PENGARUH KOMPETENSI, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN KABUPATEN BIMA - Jidan Alfian; Mukhlis; yusuf, Muhammad (Jurnal Nusa Manajemen, 2026)
This study aims to determine the influence of Competence, Work Discipline, and Job Satisfaction on Employee Performance at the Bima Regency Maritime Affairs and Fisheries Service. The approach used in this study is an associative approach. The population in this study amounted to 101 people, with a sample of 70 ASN (State Civil Apparatus), 10 P3K (National Civil Service), and 21 Honorary. The research sample used 80 people. Data collection techniques used were observation, questionnaires, and literature studies. Data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, T-tests, and F-tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study indicate that Competence (X1), Work Discipline (X2), and Job Satisfaction (X3) simultaneously have a significant effect on Employee Performance at the Bima Regency Maritime Affairs and Fisheries Service.